Acute promyelocytic leukaemia and Hodgkin's disease in the same patient. - Flanagan, N G (1994)
Acute non-lymphocytic leukaemia is a well recognised and increasingly reported complication of treated Hodgkin's disease. The prognosis is generally poor with a disappointing response to chemotherapy. A patient in whom myelodysplastic features appeared after treatment for Hodgkin's disease, to be followed shortly afterwards by acute promyelocytic leukaemia, is reported. Complete remission was achieved and sustained until Hodgkin's disease reappeared three years later when the patient was autografted with a marrow harvested four years earlier. The patient remains in good health with platelet support at the time of writing.